VOLCANIC ERUPTION EVOLUTION: A THEORETICAL TREATMENT - Slezin Yu.B. (My University, 1997)
Successive changes in the main eruptive phases and flow rate variations are analyzed for volcanoes with different characterics of magmatic systems using a numerical model for the eruption process. The main factors that control the evolution are taken to be pressure variation in the magma chamber, volcanic conduit conductivity, conduit length, and magma properties. A relationship between the latter three factors is discussed. Maps of regimes for different magmatic systems are plotted to describe the eruption evolution using a descriptive point moving in the map plane. A particular emphasis is given to the region of instability and sudden flow rate changes. A standard set of evolution scenarios is described as a function of the main evolution-controlling factors. Deviations from a standard scenario, caused by external factors such as a cone collapse, lateral magma intrusions and flank eruptions, etc. The effect of extra accidental factors is interpreted through their effects on the main factors. This theoretical analysis is based on the description of real events observed during eruptions.